Marketing internetowy w British American Tobacco Polska - Pizło, Wojciech (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2006)
The paper presents the use of the Internet marketing actions in enterprise British American Tobacco Polska. In the paper the organization of virtual marketing in the ram of corporate mission and strategy and take development of Internet marketing was shown. In the end of paper the relationship between classical marketing and Internet marketing and using Internet marketing in the future was presented